CREATION OF HEAT-EFFICIENT CERAMIC PRODUCTS FROM LOCAL MELTING RAW MATERIALS - SUBBOTA, ІRYNA; SPASONOVA, LARYSA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article is devoted to the study of the physical and mechanical properties of building ceramics made on the basis of low-melting clay of the Kyiv region with the addition of coal beneficiation waste. The expediency of using man-made raw materials of coal waste for the production of heat-efficient building ceramics is considered. Currently, the development of technological solutions for the use of coal beneficiation waste as a man-made raw material, which is effective when used in the production of ceramic products, is relevant. The reason for this was the reduction of the raw material base of high-quality clay raw materials, the increase in the cost of its use in the production of wall ceramics, a large number of reserves of various types of man-made raw materials of the coal range, which had accumulated. During the study the impact of the introduction of coal beneficiation waste on the main technological properties of ceramic masses and the physical and mechanical characteristics of finished products and the optimization of the main technological parameters of ceramics production with their application wereinvestigated. The addition of coal beneficiation waste to the composition of ceramic masses based on low-melting clays in order to improve the physical and mechanical characteristics of the finished products has confirmed its effectiveness. Coal beneficiation waste contributes to the formation of low-melting eutectics, reduces the refractoriness of amorphous silica and has a positive effect on the sintering process, forming a glass phase in the ceramic matrix. The conducted research shows that the local polymineral clay raw materials with the development of technological regimes can be used for the production of construction ceramics, which will be so necessary in all regions of Ukraine after the end of martial law for the restoration of the country.
Keywords: ceramic building materials; low-melting clay raw materials; firing; coal beneficiation waste; mechanical strength